AB0393 EFFICACY OF HYDROXYCHLOROQUINE FOR LUPUS NEPHRITIS IN MAINTENANCE PHASE. (13th June 2020) - Watanabe, M.; Haji, Y.; Kato, M.; Ito, T.; Banno, Y.; Okada, M.
Abstract : Background: Hydroxychloroquine (HCQ) is an essential drug for systemic lupus erythematosus. But in Japan, chloroquine and HCQ remain unavailable until mid 2015 because of a series of lawsuits about its retinal toxicity in the 1970s. There is insufficient knowledge regarding renal protective effect of HCQ. Objectives: We aimed to investigate its efficacy of adding HCQ for Lupus nephritis (LN) as a maintenance-phase therapy. Methods: We conducted an observational retrospective cohort study included patients with LN (n=42) in maintenance-phase in Japan. We reviewed medical records of LN patients aged > 18 years who were initiated HCQ from May 2015 to May 2018. Maintenance phase was defined as stabilization in serum creatinine and urinary segment after induction therapy and who achieved complete or partial remission. The annual change of proteinuria was compared between patients on HCQ who have proteinuria (>0.5g/gCr) or not. Other outcome measures were disease flare, dose of steroids, renal and immunologic features. Results: A total of 42 patients were analyzed and allocated to two groups based on their amount of daily urine protein level: HCQ with proteinuria as group A (>0.5g/gCr, n=14) and HCQ without proteinuria as group B(≦0.5g/gCr, n=28). Both groups were comparable, with mean (SD) age of 36.1 (12.9) years and 37.5 (13.8), female 78.6% and 92.9% in each group, mean (SD) disease duration until HCQ of 3.5 (3.25) and 3.3 (2.9) years in group A and group B, with prednisolone dose at base line of 10.3 (7.1) mg and 7.9 (4.4) mg, respectively. The mean (SD) proteinuria at base line was 1.38 (1.11) g/gCr in group A and 0.20 (0.09) g/gCr in group B and after 12 months, proteinuria decreased in group A (-1.34 g/gCr in group A vs +0.03 g/gCr in group B; p<.001;95% CI, 0.305-0.736). No relapse was experienced in group A during the study period. Conclusion: In patients with clinically stable LN but with proteinuria, hydroxychloroquine is a good therapeutic option for achievement of complete remission. Disclosure of Interests: None declared